Montezuma Quail Management in Arizona - James R. Heffelfinger; Ronald J. Olding (National Quail Symposium Proceedings, 2017)
The Montezuma quail (Cyrtonyx montezumae meamsi) has substantially different habitat requirements than other quails found in the U.S. They inhabit evergreen oak woodlands of mountain ranges in the Southwest and feed primarily on underground bulbs and tubers. Populations respond to summer precipitation because the vegetation which provides food and cover for Montezuma quail flourishes after the summer rains. Moderate to heavy grazing increases availability of Montezuma quail food plants, but resultant lack of cover precludes use of such sites. Montezuma quail avoid areas with greater than 50% forage utilization by ungulates. As with other Arizona quail species, hunting has been shown to have limited or no impact on the population level during the following years. Birds may be depleted in localized areas temporarily, but available habitat is re-occupied when pre-nesting dispersal occurs. Annual pre- and posthunt flush counts were conducted 1988-1996 by the Arizona Game & Fish Department, United States Forest Service, volunteers, and local quail hunters. Average covey size decreased during the hunting season, but the magnitude of the decrease was similar in unhunted populations. Montezuma quail populations fluctuate in response to habitat and weather conditions. A state-wide hunter questionnaire program estimated total harvest trends for Arizona. In addition, wing collection barrels had been placed in heavily hunted areas from 1981 to 1996 to obtain hunter-effort information and sex/age characteristics of the harvest. Data from these wings indicate average percentage of juveniles in the harvest was higher for Montezuma quail (x = 74.4%, range = 55.9-84.9%) than other Arizona quail species, such as Gambel's (x = 65.6%, range = 23-77%). Hunters harvested an average of 2.2 Montezuma quail per day. In 3,107 hunter-days during this period, only 13 (0.4%) resulted in a limit of birds. Three of these limits occurred in 1996 when the bag limit was reduced from 15 to 8 Montezuma quail.